Go through the points - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Glossary of Biotechnology and Genetic Engineering. FAO Research and Technology Papers. 1999. 262 pp. ISBN 9251043698 US$ 16 17.60